2014
DOI: 10.1186/s12920-014-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-21-5p as a predictive marker for complete tumor regression to neoadjuvant chemoradiotherapy in rectal cancer patients

Abstract: BackgroundNeoadjuvant chemoradiotherapy (nCRT) followed by radical surgery is the preferred treatment strategy for locally advanced rectal cancer. However, complete tumor regression is observed in a significant proportion of patients after nCRT, making them ideal candidates for alternative treatment strategies to this considerably morbid procedure. Identification of such patients based on clinical findings (complete clinical response - cCR) is difficult mainly because it relies on subjective clinical and imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 54 publications
6
67
1
Order By: Relevance
“…2 transcripts miR-519c-3p and miR-561 predicted good versus poor response with a median accuracy of 100% 20 fresh rectal biopsy samples [115] Neoadjuvant chemotherapy (capecitabine or infusional 5-FU) and radiotherapy miR-215, miR190b and miR-29b-2 were overexpressed in non-responders while let-7e, miR-196b, miR-450a, miR-450b-5-p and miR-99a were overexpressed in responders (Mandard) 85 formalin-fixed paraffin embedded post-treatment samples [116] Neoadjuvant chemotherapy (capecitabine) and radiotherapy miR-21, miR-99, miR-125b, miR-125b1, let-7c and miR-490 upregulation correlated with TRG 1-2 (Mandard). miR-21 and miR-125a-3p downregulation correlated with TRG 4 40 formalin-fixed paraffin embedded biopsy and post-treatment samples [117] Neoadjuvant chemotherapy AUC (area under curve) of 0.94 [79]. Of note, they validated their findings in an independent group of patients.miRNA has been reported to be important in determination of radiosensitivity of rectal cancers to chemoradiotherapy.…”
Section: Resultssupporting
confidence: 51%
“…2 transcripts miR-519c-3p and miR-561 predicted good versus poor response with a median accuracy of 100% 20 fresh rectal biopsy samples [115] Neoadjuvant chemotherapy (capecitabine or infusional 5-FU) and radiotherapy miR-215, miR190b and miR-29b-2 were overexpressed in non-responders while let-7e, miR-196b, miR-450a, miR-450b-5-p and miR-99a were overexpressed in responders (Mandard) 85 formalin-fixed paraffin embedded post-treatment samples [116] Neoadjuvant chemotherapy (capecitabine) and radiotherapy miR-21, miR-99, miR-125b, miR-125b1, let-7c and miR-490 upregulation correlated with TRG 1-2 (Mandard). miR-21 and miR-125a-3p downregulation correlated with TRG 4 40 formalin-fixed paraffin embedded biopsy and post-treatment samples [117] Neoadjuvant chemotherapy AUC (area under curve) of 0.94 [79]. Of note, they validated their findings in an independent group of patients.miRNA has been reported to be important in determination of radiosensitivity of rectal cancers to chemoradiotherapy.…”
Section: Resultssupporting
confidence: 51%
“…This suggests that miR-21-5p may be associated with the progression of CC malignancy. The results were corroborated by previous studies, which produced similar results (3,(9)(10)(11)(12). Notably, it was identified that miR-21-5p stimulates the proliferation and migration of CC cells through inhibition of the PTEN pathway (3).…”
Section: Discussionsupporting
confidence: 80%
“…A prior study demonstrated the association of miR-21-5p overexpression with tongue cancer cell chemo-resistance via cell adhesion molecule 1 targeting (9). miR-21-5p overexpression has also been identified as a possible predictor of tumor regression following chemoradiotherapy in patients with rectal cancer (10), and as a biomarker of recurrence in young patients with gastric cancer (11) and thymic epithelial tumors (12). It has been reported that the competing endogenous regulation of miR-21-5p by the long non-coding RNA maternally expressed 3 inhibits CC cell proliferation and apoptosis (13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been recently reported that miR-21 and SATB1 could predict complete response to preoperative CRT in rectal cancer patients. Despite that it is a wellconducted study showing very interesting findings, the relative short number of cases included in the training (n=27) and validating groups (n=16) makes necessary to further investigate the miR-21 prognostic value [33]. Finally, recent works highlight the potential clinical significance of circulating miR-21 in colorectal cancer patients [34,35].…”
Section: Discussionmentioning
confidence: 96%